ISLAMIC POPULISM IN POST-TRUTH INDONESIA - Rubaidi Rubaidi (Sayyid Ali Rahmatullah Tulungagung State Islamic University, 2020)
This article examines the rise of Islamic populism in post-truth Indonesia. It particularly discusses the proliferation of Islamic populism narratives in social media that lead to hoaxes and hate speeches which appeared in series of political elections. This article argues that there has been a similar pattern of Indonesian form of populism to that of other parts of western countries, particularly the US and the UK. Like populism in the latter two countries, the issue of “indigeneity” has generated the reproduction of post-truth narrates, ranging from false-news, hoaxes, and hate-speeches, blaiming the so-called “foreign” elements of the country. Islamist mobilisation is central to explain the proliferation of post-truth politics which cultivates tensions and divisions among society and reserves as a threat to democratic consolidation in contemporary Indonesia.